The Efforts of the Office of the Religious Affairs of South Palu in Resolving Marriage Conflicts - Ismail Ismail; Abidin Abidin; Lukman Lukman (INTERNATIONAL JOURNAL OF CONTEMPORARY ISLAMIC LAW AND SOCIETY, 2019)
This study discusses the efforts of the Office of the Religious Affairs (KUA) South Palu District to resolve marital conflict in the district. This research uses a descriptive qualitative approach where different data collection techniques are employed such as observation, interview, and document reviews. Data analysis used applies data reduction, data presentation, and data verification while consistently considering its validity. The results of this study indicate that the efforts of the KUA of South Palu District in settling down marriage conflict while disseminating the marriage law No. 1, 1974 to the community.At the time of giving marriage counseling and in other religious events such as regular recitation held at the local mosque the head of the KUA do not forget to provide explanations to the public about the adverse impacts on marital conflicts. He also highlights the importance of maintaining a harmonious family. Furthermore, the head of the KUA and his staff continuously do marriage counseling to inculcate the understanding of the importance of maintaining harmony in the household to the people in public especially to prospective brides and bridegrooms. The head of the KUA and his staff also provide guidance in regard to the rights and obligations of a husband and a wife, parental responsibilities to children. The KUA provides supports, adequate facilities, and infrastructure, cooperation with other institutions, availability of regulations that support the implementation of the KUA programs. In addition,a commitment to accountable leadership as a determining factor in the attempts of the KUA to achieve the objectives within which the form of acceleration of the Commitment of the Head of the KUA, Penghulu, or in charge person to be either a guardian of a bride or to hold a marriage, and the role of religious figures in the community are the main goals of the office of the religious affairs.